An integrated pharmacokinetic study of Dengzhanxixin injection in rats by combination of multicomponent pharmacokinetics and anti-myocardial ischemic assay. Issue 44 (13th August 2019) - Huang, Jianyong; Su, Ya; Yang, Chunlei; Li, Shaoguang; Wu, Youjia; Chen, Bing; Lin, Xinhua; Huang, Liying; Yao, Hong; Shi, Peiying
Abstract : The integrated pharmacokinetic study of Dengzhanxixin injection in rats could reveal its overall in vivo process. Abstract : This study aimed to investigate the integrated pharmacokinetics (PK) of Dengzhanxixin injection (EBI) in rats by combination of multicomponent PK and pharmacological assays. First, the protective effects of 13 main components (30 mg kg −1 per day, i.v. for 7 days) on isoprenaline-induced myocardial infarction (MI) in mice were evaluated by measuring electrocardiogram and serum creatine kinase (CK) activity, and observing cardiac pathological changes. Second, the quantitative analysis method of the main components in rat plasma was established and applied to pharmacokinetic study of EBI in rats (0.72 mL kg −1 and 3.2 mL kg −1 of 10 times concentrated EBI, single i.v.). Third, based on the multicomponent PK and anti-MI effects, PK markers were selected, and the integrated PK of EBI in rats were investigated using "plasma drug concentration sum method" and "AUC weighting integrated method". In the in vivo anti-MI study, the ST segment elevation seldom occurred and the serum CK significantly decreased ( P < 0.05 vs. model group); additionally tissue sections showed mild edema and inflammatory infiltration, and there was a little loss of striations in heart tissue in scutellarin, 3-caffeoylquinic acid (3-CQA), apigenin-7- O -glucuronide (A-7- O -G) and 4, 5-dicaffeoylquinic acid (4, 5-diCQA) treated groups, suggesting that scutellarin, 3-CQA, A-7- O -G and 4, 5-diCQA were the main anti-MI effective substances. In the PK study, the systematic exposure level of scutellarin, erigoster B, 3, 4-diCDOA (or 4, 9-diCDOA), A-7- O -G, and 4, 5-diCQA is relatively high. Considering the contents in EBI, anti-MI efficacy and PK properties of each component, scutellarin, 3-CQA, A-7- O -G, erigoster B, 3, 4-diCDOA (or 4, 9-diCDOA) and 4, 5-diCQA were selected as pharmacokinetic markers to characterize the integrated pharmacokinetic behavior of EBI in vivo . The integrated pharmacokinetic study of EBI in rats could reveal the overall in vivo process and improve the safety and rationality of the clinical use of EBI.